Indonesia : Private Sector Development Strategy - World Bank (Washington, DC, 2013)
The report reviews the Bank's private sector development strategy in Indonesia, stipulating that the country's potential will not be realized without a pattern of private sector activity, - different from the past - but, taking the opportunity offered by the crisis to make fundamental changes in the business environment, and in how business is conducted. The first priority calls for the banking, and corporate sectors to speed up the resolution of corporate debt, and ease financial flows for investment, and working capital to resume. Second, the structural inefficiencies, partly conducive to the crisis, and to its long lasting effect, need to be overcome; therefore, reforms should enable Indonesia to become a modern market economy, able to avoid future crises. This encompasses fighting corruption in the public administration, ensuring the rule of law through the court system, reinforcing property rights, and dispute resolution mechanisms, and, ensuring transparency and corporate governance. Third, broad-based, and sustainable economic growth need to be ensured by measures such as removal of obstacles to small, and medium enterprise (SME) activity, as well as SME development promotion, including physical, and social infrastructure building. Finally, the creation of an infrastructure, and regulatory framework to take full advantage of new information/communications technologies, is paramount.